Rapid and Sensitive Detection of Shigella spp. and Salmonella spp. by Multiple Endonuclease Restriction Real-Time Loop-Mediated Isothermal Amplification Technique - Wang, Yi; Wang, Yan; Luo, Lijuan; Liu, Dongxin; Luo, Xia; Xu, Yanmei; Hu, Shoukui; Niu, Lina; Xu, Jianguo; Ye, Changyun (Frontiers in Microbiology, 2015)
Shigella and Salmonella are frequently isolated from various food samples and can cause human gastroenteritis. Here, a novel multiple endonuclease restriction real-time loop-mediated isothermal amplification technology (MERT-LAMP) were successfully established and validated for simultaneous detection of Shigella strains and Salmonella strains in only a single reaction. Two sets of MERT-LAMP primers for 2 kinds of pathogens were designed from ipaH gene of Shigella spp. and invA gene of Salmonella spp., respectively. Under the constant condition at 63°C, the positive results were yielded in as short as 12 min with the genomic DNA extracted from the 19 Shigella strains and 14 Salmonella strains, and the target pathogens present in a sample could be simultaneously identified based on distinct fluorescence curves in real-time format. Accordingly, the multiplex detection assay significantly reduced effort, materials and reagents used, and amplification and differentiation were conducted at the same time, obviating the use of postdetection procedures. The analytical sensitivity of MERT-LAMP was found to be 62.5 and 125 fg DNA/reaction with genomic templates of Shigella strains and Salmonella strains, which was consist with normal LAMP assay, and at least 10- and 100-fold more sensitive than that of qPCR and conventional PCR approaches. The limit of detection of MERT-LAMP for Shigella strains and Salmonella strains detection in artificially contaminated milk samples was 5.8 and 6.4 CFU per vessel. In conclusion, the MERT-LAMP methodology described here demonstrated a potential and valuable means for simultaneous screening of Shigella and Salmonella in a wide variety of samples.